(untitled) (Journal of Plant Disease Sciences, 2025)
Maize (Zea mays L.), a major cereal crop, is susceptible to several seed-borne fungi, including Fusarium moniliforme, Alternaria alternata, Bipolaris maydis, Aspergillus spp. and Rhizopus spp., which significantly reduce seed viability and seedling vigour. Pathogenicity tests confirmed the harmful effects of these fungi on seed health. The present study aimed to manage maize seed-borne mycoflora using fungicides and biocontrol agents, with emphasis on Fusarium moniliforme and Alternaria alternata. The poisoned food technique revealed that carbendazim 25% + mancozeb 50% WS was the most effective against Fusarium moniliforme, achieving 91.10% inhibition at 0.05% concentration and complete inhibition at higher concentrations (0.1% and 0.15%). Metalaxyl 35% WS followed with inhibition up to 88.80%, while carboxin + thiram 75% WP and azoxystrobin 23% SC showed moderate efficacy. Metalaxyl 8% + mancozeb 64% WS was the least effective. Against Alternaria alternata, carboxin + thiram 75% WP achieved 100% inhibition at all tested concentrations, closely followed by carbendazim 25% + mancozeb 50% WS at 0.15%. Azoxystrobin 23% SC and metalaxyl 8% + mancozeb 64% WS showed moderate activity, whereas metalaxyl 35% WS was the least effective.Among the biocontrol agents, Trichoderma harzianum was the most effective, suppressing Fusarium moniliforme and Alternaria alternata by 68.35% and 74.41%, respectively. Trichoderma asperellum and Bacillus subtilis provided moderate control, while Pseudomonas fluorescens exhibited the least antagonistic activity.